Optimizing Decision-making in Travel through an Information Literacy Approach - Prasetyo, Hendi; Irawati, Novi (Ideas Publishing, 2025)
In the digital age, where there is a wealth of frequently unreliable information, information literacy is essential to tourists’ decision-making processes. This study aims to examine the importance of information literacy in relation to travel decisions and the variables that affect them. Using a qualitative approach through literature review, this study gathered and analyzed various relevant sources about information literacy and tourist behavior. The findings indicate that tourists with higher levels of information literacy are better equipped to evaluate the credibility of sources, make informed decisions, and understand sustainability aspects that influence conservation behavior. Therefore, improving information literacy in tourism is crucial and should involve cooperation with educational institutions to enhance tourist experiences and promote sustainable tourism.